On the Problem of Corporate Strategies of Development for Human Resources - Mykhailyshyn, Lilia; Korovchyk, Yurii; Leliuk, Olga (Journal of Vasyl Stefanyk Precarpathian National University, 2019)
The article defines the theoretical aspects of the formation of corporate development strategies of human resources and the research features of the development system of human resources at the Academy DTEK. Conceptual approach to providing continuous professional development of human resources of the enterprise is offered